Development competencies tools for an information literacy program in school libraries - Marzal, Miguel Ángel; Sellers de los Ríos, Nieves (Revista General de Información y Documentación, 2012)
Considering the fact that the competences on information issues are the main purpose of the information programmes as well as an essential element in the development of the knowledge Society, this article proceeds to reflect on the necessary basis for the effectiveness of these programmes, defining accurately, for their better application, the evolution of the competences in their use in the information units, the educational digital libraries model and the qualities of the teaching materials on the web. Then, we proceed to present a methodological proposal in order to add enough instruments to help in the exercise of competences of the information literacy programmes on a school environment and in the atmosphere of a school library (such as CREA, Teaching and Learning Resources Centres), analyzing digital libraries models and educational digital platforms.